Echocardiographic and electrocardiographic parameters during the normal postpartum period in toy breeds of dogs - Batista, Pablo Rodrigo (2017)
The aim of this study was to evaluate echocardiographic and electrocardiographic parameters during the normal canine postpartum period. Twenty clinically healthy pregnant bitches of toy breeds (11 Miniature poodles, five Yorkshire terriers, two Maltese terriers and two Bichons Frises) were evaluated on days -3, 3, 10, 17, 24, 38, 52 and 80 relative to parturition (day 0). During the first postpartum week, the width of the interventricular septum in systole, the shortening fraction and the left atrium size decreased, while the left ventricle internal diameter in systole and end systolic stress increased. There were progressive decreases in the velocity of circumferential fibre shortening, stroke volume, cardiac output, and mitral E and A wave values. Systolic blood pressure increased markedly during the first postpartum week to gradually increase thereafter. Heart rate and corrected QT interval progressively decreased, while P wave amplitude increased. QRS complex amplitude decreased in the second week after parturition and then increased during the following weeks. In conclusion, there were changes in systolic function and some structural adaptive changes in the bitch during the first 80 days postpartum. In addition, maternal heart rate and corrected QT interval decreased, while P wave and QRS amplitudes increased.